Analisis Pengaruh Kebijakan Cadangan Wajib, Inflasi, Firm Size, Sales growth dan Leverage terhadap Stock return pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Susanti Susanti; Wisnu Yuwono (Politeknik Negeri Batam, 2015)
This study aimed to analyze the influence of cash reserve ratio, inflation, firm size, sales growth and leverage to stock return on banking companies listed in the Indonesia Stock Exchange.This study used a sample of 36 companies listed in Indonesia Stock Exchange during the period 2009 to 2013, in which the sample is selected using purposive sampling method. Statistical method used in analyzing the data is the multiple regression models. Results of this study showed that only cash reserve ratio and inflation in this study show negative significant effect on stock return, while firm size has a positive significant effect o stock retrun. The results of this study showed some implications for investors, investors are more cautious in considering these factors before investing at banking sector.